Compensation of the spatial deviations of measuring elements in CAD - Stanovskyi, Olexandr; Toropenko, Alla; Lebedeva, Elena; Dobrovolska, Viktoriya; Daderko, Olesya (Technology audit and production reserves, 2017)
The object of research is the processes of computer-aided design of the elements of complex measuring instruments intended to work under conditions of significant deviations in space caused by mechanical or thermal stresses. One of the most problematic places is that any protection state completely eliminates unwanted deviations of the elements. This is especially true for measurement objects that have large dimensions (tens of meters) and weight, opacity, high temperatures (hundreds of degrees), significant external influences of unpredictable nature, and the like. Models of behavior of such objects under load are extremely complex, and methods of their analysis and use in CAD are not available at all, which leads to the laying of significant errors of the future measurement already at the design stage. In the course of the study, the theory of analysis of technical systems, the theory of measurements, the theory of the resistance of materials and oscillations, the theory of computer-aided design were used. To develop a capacitive method for measuring the density of parts of large-sized reinforced concrete objects from heterogeneous materials, methods of pattern recognition and a virtual object are used. Theoretical and experimental virtual models of electrical characteristics of the elements of measuring instruments and models of their deviation are obtained. Models are used in automated design systems for complex means of capacitive measurement of concrete. The first is mathematical, in which compensation is performed solely by making changes to the measurement results. The second is mechanical, in which compensation is made by changing the geometry of the measuring tool (with static deviation) or depreciation of their elements (with dynamic). Thanks to this, it is possible to create a new subsystem of CAD «DEVICOM», with the help of which shock absorbers were designed to control the technological process of manufacturing the reinforced concrete product «Power transmission line support», which, as a result, reduced the amount of defective products by 7.4 %.